DEVELOPMENT OF GEOPOLYMER COMPOSITES WITH BIOPOLYMERS REINFORCEMENT - KAH WAI, TEOW (IRC, 2017)
Huge amount of industrial wastes being discharged from various industries. These industrial waste like fly ash, bottom ash and blast furnace slag could be further utilized and synthesized as geopolymer to reduce pollution to the mother earth nature. Geopolymer has been a great promising green alternative to cement as they provide a good strength, mechanical and thermal properties. Biopolymer reinforced geopolymer composites might be the solution to enhance the flexural strength. The main objective of this research is to determine the suitable biopolymers to blend with geopolymer to improve flexural strength. Biopolymers such as corn starch, gelatin and agar agar were chosen to be used for the synthesization of hybrid geopolymer. Different properties of the hybrid geopolymers will be characterized such as surface morphology, functional groups and flexural strength. Obtained results indicated that the hybrid composites of geopolymer have amorphous structure from SEM results. Sample E has high flexure stress (4.21 MPa) and highest elastic modulus in bending (6664 MPa). This indicates that sample E has the highest flexural strength among all the hybrid geopolymer composites. The increase of dosage of biopolymers does not increase the flexural strength of hybrid geopolymer composites. Hence, the optimum dosage of biopolymer reinforcement is 1.00%.